Health System Factors Constrain HIV Care Providers in Delivering High-Quality Care: Perceptions from a Qualitative Study of Providers in Western Kenya. (23rd January 2019) - Genberg, Becky; Wachira, Juddy; Kafu, Catherine; Wilson, Ira; Koech, Beatrice; Kamene, Regina; Akinyi, Jacqueline; Knight, Jennifer; Braitstein, Paula; Ware, Norma
The burden on health systems due to increased volume of patients with HIV continues to rapidly increase. The goal of this study was to examine the experiences of HIV care providers in a high patient volume HIV treatment and care program in eastern Africa. Sixty care providers within the Academic Model Providing Access to Healthcare program in western Kenya were recruited into this qualitative study. We conducted in-depth interviews focused on providers' perspectives on health system factors that impact patient engagement in HIV care. Results from thematic analysis demonstrated that providers perceive a work environment that constrained their ability to deliver high-quality HIV care and encouraged negative patient–provider relationships. Providers described their roles as high strain, low control, and low support. Health system strengthening must include efforts to improve the working environment and easing burden of care providers tasked with delivering antiretroviral therapy to increasing numbers of patients in resource-constrained settings.